Skenario Pengembangan Kewirausahaan Mahasiswa - M. Achmad Subing; Abdul Basit (Universitas Bandar Lampung (UBL), 2014)
The high level of unemployment in Indonesia, one of them caused by low entrepreneurial activity (entrepreneurial activity). University of Bandar Lampung (UBL) as one of the universities in Lampung province is determined to become one of the colleges that play an important role in overcoming the problem of unemployment. The efforts will be made by the UBL is to develop students entrepreneurial spirit. With the development of entrepreneurship graduates UBL is expected to have a paradigm shift in addition to the job-seekers also have the paradigm as a job-creator. The purpose of this study is to analyze the factors influencing the development of entrepreneurship students at the University of Bandar Lampung, and analyzes entrepreneurship development scenarios student at the University of Bandar Lampung. Data and information processed by using the framework of decision analysis with multiple criteria. Analysis tool used is Analytical Hierarchy Process (AHP) which data processing is done by using Expert Choice software v.11. The results showed that the development of entrepreneurship students at the University of Bandar Lampung will get optimal results when performed by nurturing relationships with employers with the advanced development scenarios based on the motivation of financial freedom (Financial Freedom). The main thing that must be developed in terms of technical factors is the market /marketing, whereas in terms of the factors is the raw material resources.Tingginya tingkat pengangguran di Indonesia salah satunya disebabkan oleh rendahnya aktivitas kewirausahaan (entrepreneurial activity). Universitas Bandar Lampung (UBL) sebagai salah satu perguruan tinggi di Provinsi Lampung bertekad untuk menjadi salah satu perguruan tinggi yang berperan penting dalam mengatasi masalah pengangguran. Upaya yang akan dilakukan oleh UBL adalah dengan mengembangkan jiwa kewirausahaan mahasiswa. Dengan pengembangan kewirausahaan ini diharapkan lulusan UBL memiliki perubahan paradigma selain sebagai job-seeker juga memiliki paradigma sebagai job-creator. Tujuan penelitian ini adalah untuk menganalisis faktor-faktor yang berpengaruh terhadap pengembangan kewirausahaan mahasiswa di Universitas Bandar Lampung, serta menganalisis skenario pengembangan kewirausahaan mahasiswa di Universitas Bandar Lampung. Data dan informasi diolah dengan menggunakan kerangka analisis pengambilan keputusan dengan kriteria majemuk. Alat analisis yang digunakan adalah Proses Hierarki Analitik (AHP) yang pengolahan datanya dilakukan dengan menggunakan software Expert Choice v.11. Hasil penelitian menunjukkan bahwa pengembangan kewirausahaan mahasiswa di Universitas Bandar Lampung akan mendapatkan hasil yang optimal apabila dilakukan dengan menjalin kerjasama dengan pengusaha dengan mengedepankan skenario pengembangan berdasarkan motivasi kebebasan keuangan (Financial Freedom). Hal utama yang harus dikembangkan dari segi faktor teknik adalah market/marketing, sedangkan dari segi faktor sumberdaya adalah bahan baku.